POPULATION DYNAMICS OF GIANT AFRICAN SNAIL, ACHATINA FULICA BOWDICH (STYLOMMATOPHORA: ACHATINIDAE) AND ITS CORRELATION WITH WEATHER PARAMETERS - PRITI KUMARI; M. L. AGARWAL; NAGENDRA KUMAR (The Bioscan, 2015)
Maximum giant African snail, Achatinafulica population(94.20 snails/25 m 2 ) was recorded in 39 th standard week of 2008 and subsequently a decrease in snail population was recorded which reached to its lowest level (4.20 snail/25 m 2 ) by 47 th standard week. Combined effect of weather factors on A. fulica population was 74 per cent (R 2= 0.74).Pest population was positively correlated with maximum and minimum temperatures(r= 0.203 and 0.659**). Similarly humidity also showed a positive and significant relationship with snail population (r = 0.367* and 0.687**). In 2009 snail population showed similar trend as that of previous year and cumulative effect of weather factors on population dynamics of A. fulica was 62 per cent (R 2= 0.74). Optimum conditions of good summer rainfall and increase relative humidity provided favourable environment for multiplication of snail